2011
DOI: 10.1007/s11121-011-0255-0
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Unhealthy Behaviors in the Aerobics Center Longitudinal Study

Abstract: BackgroundClustering of unhealthy behaviors has been reported in previous studies; however the link with all-cause mortality and differences between those with and without chronic disease requires further investigation.ObjectivesTo observe the clustering effects of unhealthy diet, fitness, smoking, and excessive alcohol consumption in adults with and without chronic disease and to assess all-cause mortality risk according to the clustering of unhealthy behaviors.MethodsParticipants were 13,621 adults (aged 20–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 54 publications
(108 reference statements)
5
35
0
3
Order By: Relevance
“…Research suggests that risk behaviors tend to cluster within individuals (12,14,24,51). Likewise, our results showed that smoking men were less vigorously active than their nonsmoking peers.…”
Section: Discussionsupporting
confidence: 62%
“…Research suggests that risk behaviors tend to cluster within individuals (12,14,24,51). Likewise, our results showed that smoking men were less vigorously active than their nonsmoking peers.…”
Section: Discussionsupporting
confidence: 62%
“…Failure to model this accumulation of adversity may fail to capture, and effectively address, the full burden of social exposure. Unhealthy behaviors such as poor nutrition, physical inactivity, cigarette smoking and excessive alcohol intake are clustered in individuals with and without chronic diseases (Héroux et al, 2012). Similarly, discrimination and other psychosocial stressors are clustered with each other and co-occur more frequently in disadvantaged racial populations (Sternthal, Slopen & Williams, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Clustering of cardiovascular disease risk factors, which imparts an even greater risk than the sum of the individual risk factors in adults, also takes place in childhood and tracks into adolescence, as shown in this study. For instance, it could be shown that unhealthy diet, fitness, smoking, and excessive alcohol consumption were related to each other among adults [11] and that the presence of these factors was related to cardiovascular disease mortality. [12] Moreover, skipping breakfast seems to co-occur with other unhealthy lifestyle habits such as smoking and physical inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Parental factors such as physical inactivity, [9] smoking [9] and overweight also contribute. [10] Because these individual factors are not independent of each other and often appear in combination, [11] it is important to know their combined impact on CVR. This has been shown in a prospective study in adults in which the relative risk of cardiovascular disease mortality increased with a decreasing number of positive lifestyle factors such as healthy eating, a physically active lifestyle, low alcohol consumption and the absence of smoking.…”
Section: Introductionmentioning
confidence: 99%